A blockchain framework using proof of authority and smart contracts for ethical and secure healthcare asset management - Shaikh, Muhammad Farooq; Hassan, Syed Hamza; Maccaro, Alessia; Pratesi, Giacomo; Piaggio, Davide (Frontiers in Public Health, 2025)
The proposed model in this paper focuses on asset tracking and monitoring in the healthcare industry and it uses blockchain technology. Data security incidents in the healthcare field have created financial and ethical problems over the last few years. During 2024, the money lost from healthcare data breaches often exceeded 4.88 million due to the exposure of private patients and asset information. This shows why it is important to use secure systems to protect worthwhile information and manage key assets efficiently and correctly. Since such intrusions cannot be prevented by the current systems, businesses end up losing money and working less efficiently. These issues are addressed by using a system that includes blockchain, IoT and digital asset tracking technologies. To ensure data integrity and prevent fake information, Proof of Authority (PoA) uses chosen, recognized authorities to verify and confirm each transaction. To protect transactions, PoA requires a number of approvals from different parties which helps ensure that transactions are safe and secure. With immutable and decentralized features, blockchain makes the management of assets more secure and transparent. Records of asset transfers and data are safely stored on the blockchain with smart contracts, providing real-time monitoring and no room for errors. When integrated with IoT devices, the system can constantly check all the assets, improving the company’s efficiency while reducing losses of items. The findings suggest that a PoA blockchain system can help healthcare asset management systems operate more ethically, safely, transparently, and efficiently.